Field germination and productivity of hard and soft spring wheat at application of mineral fertilizers in Forest-Steppe of Ukraine - Антал, Т. В.; Гарбар, Л. А.; Малеончук, О. В.; Корпан, А. С.; Трет'як, Д. А. (Scientific Progress & Innovations, 2016)
The results of researches of influencing of mineral fertilizers under hard and soft wheat on the field germination and productivity for growing in the Forest-Steppe of Ukraine are presented in the article. We found that in the Forest-Steppe of Ukraine on deep black soil with a low humus content and black ashed soil the field germination of plants depends on weather terms, predecessor and system of fertilizer. We proved that in variants with bringing of phosphoric and potassium fertilizers the field germination of seed was on 4–5 % more high comparatively with variants without fertilizers. The germination of spring wheat seed goes down on the average on 0,4–1,2 % with the increase of norm of sowing of seed from 3,0 to 7,0 million units per hectare.